2010
DOI: 10.1590/s1807-59322010001100013
|View full text |Cite
|
Sign up to set email alerts
|

Depression during pregnancy in women with a medical disorder: risk factors and perinatal outcomes

Abstract: BACKGROUND:Approximately one‐fifth of women present depression during pregnancy and puerperium, and almost 13% of pregnant women experience a major depressive disorder.OBJECTIVE:The aim of this study was to identify risk factors for depression among pregnant women with a medical disorder and to evaluate the influence of depression on perinatal outcomes.METHODS:Three hundred and twenty‐six pregnant women with a medical disorder were interviewed. A semistructured interview was conducted for each participant usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 21 publications
2
37
1
13
Order By: Relevance
“…Estudos sobre o tema identificaram que mulheres que apresentaram alguma complicação clínica durante a gravidez tiveram maior probabilidade de desenvolver depressão, o que pode ser explicado pela maior fragilidade em que a mulher se encontra ao enfrentar problemas de saúde durante a gestação 20,26 . Vale ressaltar que o efeito dos fatores de suporte profissional e a tendência linear se mantiveram ainda após o ajuste com as variáveis que mediam a morbidade das gestantes.…”
Section: Epds < 10 Prevalência (%)unclassified
“…Estudos sobre o tema identificaram que mulheres que apresentaram alguma complicação clínica durante a gravidez tiveram maior probabilidade de desenvolver depressão, o que pode ser explicado pela maior fragilidade em que a mulher se encontra ao enfrentar problemas de saúde durante a gestação 20,26 . Vale ressaltar que o efeito dos fatores de suporte profissional e a tendência linear se mantiveram ainda após o ajuste com as variáveis que mediam a morbidade das gestantes.…”
Section: Epds < 10 Prevalência (%)unclassified
“…29 This study found a high rate (16%) of ideations that it would be better to die or somehow hurt oneself, which is indicative of a specific risk for suicide. A study conducted using the PRIME-MD to interview pregnant women with complicating conditions at the same health center as the one in this study found that 5% of the study population was at risk for suicide.…”
Section: ■ Materials and Methodsmentioning
confidence: 68%
“…It has also been reported that multigravidas, women with current and past obstetric complications and history of previous abortions can also attribute to depression. Many studies support these facts [3,4,6,7,9].…”
Section: Depressionmentioning
confidence: 85%
“…Others can be age, marital status, parity, unwanted pregnancy, lack of social support, etc. [3][4][5][6][7][8][9][10]. Obese woman are more likely to experience elevated antenatal and postpartum depression [11].…”
Section: Risk Factorsmentioning
confidence: 99%